Odpowiedzi

2009-10-11T14:18:20+02:00
A) 0,17 × (-2) = 0,34
b) -1¼ × (-4) = -5/4 × (-4) = 5
c)-6⅔ : 2 = -20/3 : 2 = -10/3 = -3 1/3
d)-0,2 × (-0,2) = 0,04
e)-3⅓ × (-3) = -10/3 × (-3) = 10
f)-3,75 : (-3) = -15/4 : (-3) = 5/4 = 1 1/4
g) (-3)² × ⅓ = 3
h) (⅓)² × (-9) = -1
i)-6² : ½ = -72 (lub 72, jak - też jest pod potęgą)
j) 3¾ : (-1,25)² = 15/4 : (-5/4)² = 12/5 = 2,4
Najlepsza Odpowiedź!
2009-10-11T14:19:39+02:00
A) 0,17 × (-2)=-0,34
b) -1¼ × (-4)=-1,25×(-4)=5
c)-6⅔ : 2=-20/3×1/2=-10/3=-3 i 1/3
d)-0,2 × (-0,2)=0,04
e)-3⅓ × (-3)=-10/3×(-3)=10
f)-3,75 : (-3)=1,25
g) (-3)² × ⅓=9×1/3=3
h) (⅓)² × (-9)=1/9×(-9)=-1
i)-6² : ½=-36×2=-72
j) 3¾ : (-1,25)² =3,75:1,5625=2,4
1 5 1